The features of the application of Islamic banking in foreign countries (Journal of Economic Research & Business Administration, 2016)
The special features of Islamic finance include the following: involvement of liquid capital; transaction based on principles such as a reliability, honesty, truthfulness and transparency; project income and risks are divided between the parties to the transaction; financial flows linked to real assets; the absence of speculative; the development of production capacities and economic infrastructure. In this regard, developed and developing countries are actively implementing Islamic finance in recent years. Advanced countries are interested in Islamic banking, Islamic securities, the advantages of Islamic investment. It is not the secret that the role of Western foreign experience, which was the basis of the world economic and financial system, becomes weak today. According to experts opinion, the main drawback of the European example is credit interest rates. While the countries that have built their financial system based on Islamic principles, they are not so much affected by the crisis. Financial experts explain this with respect to the advantage of the Islamic financial system.
Keywords: Islamic banking; Islamic finance; investment; derivatives; investors; investment project.